P0048THE EFFECT OF GENOTYPING ON THE NUMBER OF PHARMACOTHERAPEUTIC GENE-DRUG INTERVENTIONS IN CKD3-5 PATIENTS. (6th June 2020) - Kerskes, Marieke; Van den Eijnde, Carien; Deiman, Birgit; Aarnoudse, Albert-Jan; Grouls, Rene; Deenen, Maarten
Abstract: Background and Aims: Most patients with CKD (Chronic Kidney Disease) 3-5 are polypharmacy patients (i.e. use of ≥5 drugs). As renal function is important for the clearance of many drugs, dose adjustment is often necessary and some drugs are even contra-indicated in patients with CKD. Many of these drugs are metabolized by cytochrome P450 (CYP-enzymes) in the liver. Several genetic mutations in these CYP enzymes are known to result in an altered metabolism capacity of drugs. Knowledge of the patients CYP450 genotype may thereby be of added value in reducing the incidence of supratherapeutic concentrations of drugs and reducing side effects, especially in this patient population with already reduced renal function. The aim of this study was to determine the added value of pharmacogenetic testing to the routine medication evaluation in polypharmacy patients with CKD3-5 disease, defined as the total number of pharmacotherapeutic interventions based on a relevant gene-drug interaction as assessed by the nephrologist and hospital pharmacist. Method: This was a prospective single-centre study in adult polypharmacy patients with CKD3-5 disease not on dialysis who visited the outpatient clinic of the Catharina Hospital Eindhoven, the Netherlands. In each patient enrolled in the study we determined a pharmacogenetic profile consisting of CYP1A2, CYP2B6, CYP2C9, CYP2C19, CYP2D6, CYP3A4, CYP3A5 and VKORC1 . A gene-drug interaction was considered as relevant based on the DPWG (Dutch Pharmacogenetics Working Group) guideline. Of all these according to the DPWG guideline relevant gene-drug interactions the treating nephrologist and hospital pharmacist assessed the clinical relevance and necessity of a pharmacotherapeutic intervention in the individual patient. Primary endpoint of the study was the total number of applied pharmacotherapeutic interventions based on a relevant gene-drug interaction. Results: A total of 61 patients were enrolled. Median eGFR in the study population was 18 ml/min. Patients used a median (range) number of 12 (5-20) drugs. Genotyping resulted in a total of 172 altered phenotypes based on a pharmogenetic mutation. We observed a total of 66 gene-drug interactions, of which 56 were considered relevant and resulted in 26 applied pharmacotherapeutic interventions in 20 (32.8%) patients. These interventions consisted of 10 dose adjustments (38.5%), 7 drug stops (26.9%) and 9 drug changes (34.6%). Conclusion: Pharmacogenetic testing leads to additional pharmacotherapeutic interventions based on relevant gene-drug interactions. This study shows that pharmacogenetic testing in CKD3-5 patients can be of added value to the routine medication evaluation, and may further optimize pharmacotherapy in this population.